Using the Chick Embryo Model to Examine the Effects of Hypoxia Pre-conditioning of Uveal Melanoma Cells on Tumor Growth and Metastasis. (3rd April 2023) - Draper, James; Alexander, Jodi; Nair, Rohini M.; Scullion, Nicole; Narayana, Revu V. L.; Aughton, Karen; Herrmann, Anne; Vemuganti, Geeta K.; Kalirai, Helen; Coupland, Sarah E.
Abstract: Purpose: Highly dynamic oxygen gradients occur within tumors that can result in a hypoxic response, contributing to tumor progression and metastasis. Evidence in uveal melanoma (UM) suggests an upregulated hypoxia response in some poor prognosis UM characterized by HIF1α signaling. We aimed to investigate the effects of exposure to hypoxia on tumor growth and dissemination in the chick embryo chorioallantoic membrane (CAM) model. Methods: UM cell lines (MP41, 92.1, MP46, and OMM1) were grown in two-dimensional culture and pre-exposed to hypoxic (1% O2 ) conditions for 72 h. The effects of this hypoxia pre-conditioning on cell number and clonogenicity as compared with 21% O2 ("normoxia") were investigated prior to transplantation of the cells onto the CAM. Nodule-forming efficiency (NFE), nodule size, and the presence/absence of tumor cell dissemination were determined macroscopically and histologically. Results: Exposure of UM cell lines to hypoxia upregulated HIF1α expression compared to cells cultured in normoxia. A 72-h pre-exposure to hypoxia significantly reduced cell number and clonogenicity in the MP41 and OMM1 cell lines while it had little effect in 92.1 and MP46 cells. When 72-h hypoxia pre-conditioned cells were grown in three-dimensions on the CAM, a reduction in NFE and nodule size was observed when compared with normoxic UM cells. All nodules were composed of proliferating (Ki-67+) Melan-A + cells and displayed chick blood vessel recruitment. Spread of UM cells into the adjacent CAM was observed; however, dissemination to the chick liver was only seen with 92.1 cells grown under normoxia. Conclusions: Hypoxia pre-conditioning does not appear to drive a metastatic phenotype in UM; however, further understanding of how oxygen dynamics within the tumor microenvironment regulates HIF1 signaling is needed to determine whether inhibitors of HIF signaling represent a therapeutic option in metastatic UM.